Methods matter: The sensitivity of Malawian poverty estimates to definitions, data, and assumptions - Ulrik Beck; Karl Pauw; Richard Mussa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper decomposes differences between the official poverty estimates of Malawi and a set of revised estimates by Pauw et al. (2016, forthcoming) with respect to five methodological differences: (i) the use of a revised set of unit conversion factors; (ii) the specification and use of regional poverty lines as opposed to a single national poverty line; (iii) the use of implicit survey-based prices rather than external price data; (iv) estimation of food separate poverty lines in the two surveys; and (v) permitting a change in the food/non-food composition of the consumption basket over time. Our results suggest that the decline in national poverty varies between 3.4 and 8.4 percentage points, compared to the official estimate of a decline of 1.8 percentage points.
Keywords: E21; I32; O12; 330; growth; poverty; Malawi; poverty measurement